Oxidation of Benzaldehydes by Quinolinium Dichromate-A Kinetic Study - Aruna, K.; Manikyamba, P.; Sundaram, E.V. (Asian Journal of Chemistry, 2010)
Oxidation of benzaldehydes (BZA) by quinolinium dichromate (QDC) in aqueous acetic acid is acid catalysed and is first order in (QDC) and also in (BZA). A cation dipole type of interaction between benzaldehyde and the oxidant is indicated. Electron-withdrawing substituent enhances the rate of oxidation while electron-donating group reduces the oxidation rate compared to the unsubstituted benzaldehyde. The rate data is correlated with σ and (σ+–σ) according to Yukawa-Tsuno equation. The products identified are the corresponding benzoic acid and Cr(III) ion. Thermodynamic parameters are computed and a probable mechanism is proposed.